Food microbiology - Ngô, Thị Phương Dung (Nxb. Đại học Cần Thơ, 2013)
In this field of food microbiology, the scope encompasses a wide variety of micro-organisms, the ecological relationships bewteen micro-organisms and foods, in both negative (spoilage) and positive (food fermentation) contexts, a broad spectrum of environmental factors influencing microbial survival and growth, the roles of micro-organisms in causing food-borne disease, impacting on food safety and the use of microbes for food production/.